INNOVATIVE METHODS OF ORGANIZING THE MUSEUM COMPLEX - Sydorchuk, Tetiana; Zhovkva, Olha (Theory and practice of design, 2023)
Formulation of the problem. The problem of designing museums lies in the obsolescence of traditional approaches and the insufficient involvement of visitors. This requires the use of innovative technologies to attract attention and attract a wide audience. The purpose of the article is the formation of innovative methods for the organization of the museum environment and the analysis of modern technologies that change the traditional understanding of the use of space. Methodology. Determined on the basis of a review of museum complexes with different functions; comparison and generalization of design experience in domestic and foreign architecture; analysis of technological support of data and systems used in modern museum design; consideration of statistical data on museum attendance and visitor interaction with exhibits. The results. Justification and determination of the advantages of innovations in museum design and their significance for modern architecture. Rational use of the potential of technologies to solve problems associated with outdated approaches and compact use of space. Scientific novelty. The research contributes to the development of the organization of the museum environment using modern technologies. Generalization and systematization of innovative methods for the popularization of museums. The practical significance lies in the expansion of knowledge and specific recommendations regarding the use of museum technologies in museum design. The provided methods should help modernize and modernize museum exhibits for active interaction of visitors and their further involvement.